If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 + -7x = 63 + -35x Solving 11 + -7x = 63 + -35x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '35x' to each side of the equation. 11 + -7x + 35x = 63 + -35x + 35x Combine like terms: -7x + 35x = 28x 11 + 28x = 63 + -35x + 35x Combine like terms: -35x + 35x = 0 11 + 28x = 63 + 0 11 + 28x = 63 Add '-11' to each side of the equation. 11 + -11 + 28x = 63 + -11 Combine like terms: 11 + -11 = 0 0 + 28x = 63 + -11 28x = 63 + -11 Combine like terms: 63 + -11 = 52 28x = 52 Divide each side by '28'. x = 1.857142857 Simplifying x = 1.857142857
| 117=9 | | 4(x^2+1/x^2)-8(x+1/x)+3=0 | | 3x-5=10-33 | | 4x+x-8+5x+10x=12 | | x^3+11x^2-5x+1=0 | | 10+2t=3t-1 | | 2805739x-45759=583428563957489667 | | 39/49*14/99*27/26 | | 8a-5=4(3a-1) | | -6(3t-5)-4(2t+6)+4t= | | v/3-v/6=2 | | -3(2-9)+13= | | 5/6*6 | | 3(3x-1)=5(2-x)+3 | | x-56409=240021 | | x+5/6=x/2+3/4 | | (-9)(-9)(-9)= | | 5t^2+t-18=0 | | -1=-7x+6 | | 9/48/(-9/8) | | 2x+-2=4 | | (-3)(-5)(-4)(-10)= | | -1=-7x+6y | | y^2+y-0=0 | | x-246=688 | | -8(-4)= | | -7(-7)+6y=-42 | | -32-(-74)= | | 2/3(12x-15)+1/4(24x-16) | | 6k-13=4k+14 | | x/3+5=x/6+18 | | -32-16-(-27)= |